Novel mutations of TEX11 are associated with non-obstructive azoospermia - Song, Jian; Sha, Yanwei; Liu, Xiaojun; Zeng, Xuhui; Zhao, Xiuling (Frontiers in Endocrinology, 2023)
Non-obstructive azoospermia (NOA) affects 10% of infertile men worldwide, and genetic studies revealed that there are plenty of monogenic mutations that responsible for a part of idiopathic NOA cases. Testis-expressed gene 11 (TEX11) is an X-linked meiosis-specific gene, many pathogenic variants in TEX11 have been detected in NOA patients, and the deficiency of this gene can cause abnormal meiotic recombination and chromosomal synapsis. However, many NOA-affected cases caused by TEX11 mutation remain largely unknown. This study reported three novel TEX11 mutations (exon 5, c.313C>T: p.R105*), (exon 7, c.427A>C: p.K143Q) and (exon 29, c.2575G>A: p.G859R). Mutations were screened using whole-exome sequencing (WES) and further verified by amplifying and sequencing the specific exon. Histological analysis of testicular biopsy specimens revealed a thicker basement membrane of the seminiferous tubules and poorly developed spermatocytes, and no post-meiotic round spermatids or mature spermatozoa were observed in the seminiferous tubules of patients with TEX11 mutation. Conclusion This study presents three novel variants of TEX11 as potential infertility alleles that have not been previously reported. It expanded the variant spectrum of patients with NOA, which also emphasizes the necessity of this gene screening for the clinical auxiliary diagnosis of patients with azoospermia.